Sharenting: Pride, affect and the day‐to‐day politics of digital mothering. Issue 4 (6th March 2019) - Lazard, Lisa; Capdevila, Rose; Dann, Charlotte; Locke, Abigail; Roper, Sandra
Abstract: The coming together of parenting and routine posting on social networking sites has become a visible and recognisable theme, and the term "sharenting" has found a place in everyday talk to describe some forms of parental digital sharing practices. However, while social media has undoubtedly provided a space for parents to share experiences and receive support around parenting, sharenting remains a contestable issue. Thus, one reading of sharenting would be as a display of good parenting as mothers "show off" their children as a marker of success. However, the term also can be used pejoratively to describe parental oversharing of child‐focused images and content. In this paper, we explore the practice of sharenting in terms of pride, affect and the politics of digital mothering in a neoliberal context to conclude that sharenting can be best understood as a complex affective and intersectional accomplishment that produces motherhood and family as communicative activities within digital social practices.